Administrative and Technological Innovation: The Indirect Effects of Organizational Culture and Leadership - Hakyeon Lee; J.S. Butler; Joowon Jeong (Transylvanian Review of Administrative Sciences, 2023)
Administrative innovation is defined as changes to the rules and structures that characterize the communication methods and work of employees within an organization, and technological innovation refers to the implementation of programs and services. This study examines the relationship between administrative and technological innovation using two environmental factors, namely leadership and organizational culture, as indirect variables. Using structural equation modeling on a 2015 Korea Institute of Public Administration survey, this study finds that there are no direct effects between administrative innovation and technological innovation. However, results indicate that a strong organizational culture positively affects the relationship between administrative and technological innovation, and leadership in an organization plays a similar role to that of organizational culture. These findings suggest that changing the rules of are organization alone is not enough to lead to technological innovation, which must be supported by a strong culture and leadership.